(untitled) (Revista Nacional de Odontología, 2017)
Introduction: In Mexico, the Oral Hygiene Habits Scale (ohhs) has been recently developed; its internal consistency and factorial structure have been determined, but its distribution has not been described. Aim: To describe the distribution of the ohhs and test its convergent validity. Method: A cross-sectional descriptive-correlational study with non-probability sampling was carried out. Two samples were recruited: One of 256 participants from the general population and another of 240 participants from the dental clinic. The ohhs was administered in both samples and the Simplified Oral Hygiene Index (ohi-s) only in the latter. Results: Distribution of the total ohhs score was equivalent between both samples and did not conform to a normal curve. In a range between 0 and 4, its median frequency corresponded to “sometimes.” ohhs scores between 0 and 0.999 (≤ 20 th percentile) allowed to identify poor oral hygiene habits; between 1 and 2.124, average habits; and between 2.125 and 4, good habits. These three intervals were: 0-1.749, 1.75-2.999, and 3-4 in tooth brushing; and 0-0.249, 0.25-1.249 and 1.25-4 in flossing. The correlation between ohhs and ohi-s was negative and moderate. Conclusion: The ohhs needs to be interpreted by percentiles; its central tendency (median) shows poor oral hygiene habits among the participants, mainly due to misuse of floss; and it has convergent validity, since it demonstrates that poor oral hygiene habits lead to more debris and calculus.